Análise da alfabetização científica no ensino de fitoterápicos por meio de uma sequência didática - Fernandes Neto, Larissa Soares (Universidade Federal de São Carlos, 2020)
The use of herbal medicines as a form of treatment or complement to health care is a practice that is quite present in the world population. In Brazil, the difficult access of people to health services, the high cost of industrialized medicines and the idea of using natural products that are less harmful, contribute to the growing demand for herbal medicines. However, caution is necessary, as medicinal plants have chemical substances that can cause unexpected reactions and drug interactions, which implies information and care with their administration. As they are over-the-counter products, they are subject to self-medication and pharmaceutical guidance, and it is necessary updated scientific information about their safety and effectiveness by professionals. This project have aimed to promote scientific literacy involving herbal medicines and their concepts. With the application of a planned and selected didactic sequence with varied resources, such as expository and dialogued classes, experimental, text discussion and research, for students of the technical course of pharmacy at ETEC Francisco Garcia in Mococa/SP. Data collection was performed using observational and participatory methodology, and the analysis of the research was carried out based on qualitative analysis. The students have shown learning of the contents, identification of technical-scientific terms, and development of criticality and were encouraged to seek continuous scientific updating, which promoted the training of professionals able to the job market and capable of proposing improvements around them.
Analysis of scientific literacy in the teaching of phytotherapy through a teaching sequence
Keywords: Alfabetização científica; Criticidade; Fitoterápicos; Sequência didática; Técnico-científico; Scientific literacy; Criticality; Herbal medicines; Didactic technical-scientific sequence; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::AVALIACAO DA APRENDIZAGEM